MODEL POLA LAJU ALIRAN FLUIDA DENGAN LUAS PENAMPANG YANG BERBEDA MENGGUNAKAN METODE BEDA HINGGA - Vira Marselly; Defrianto '; Rahmi Dewi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The writer has done a research on the model of rate pattern of liquid fluid flow by using flow model that has different pattern. The Equation of continuity was used to solve flow rate case, while Equation of Laplace two dimensions was used for numerical case by finite difference methods by using MATLAB R2009b (version 7.9.0.529). The purpose of fluid research was making flow pattern then analyzing fluid flow to each point in dimensions on Equation of Laplace. The methodology used in this research was evaluating Equation of Laplace concept, identifying the problems, two dimensions of Laplace equation used, completing the numerics by using finite difference methods, and completing analitics for simple cases. The results showed that there was no significant between analytical and computation of fluid flow rate. It can be seen the average of error value is close to zero and the highest error value is 0,000,778 % . Even in various geometry problems, the flow pattern can is be also visualized.